Similarities in socioeconomic disparities and inequalities in women’s nutritional status and health care in Bangladesh, Ethiopia, India, and Nigeria - Tina G. Sanghvi; Edward A. Frongillo (Global Health Action)
Background Reducing inequalities in women’s nutrition and health care can accelerate progress towards Sustainable Development Goals for maternal and child health. Nutrition interventions for women are delivered through maternal health services such as antenatal care and institutional deliveries, but whether they reach and protect the disadvantaged against malnutrition is not well documented. Objective To assess the similarities in socioeconomic disparities and inequalities in the nutritional status and health care of women. Methods We analyzed nationally representative data from Demographic and Health Surveys (DHS) conducted in Bangladesh, Ethiopia, India, and Nigeria to calculate Erreygers index. This index measures the inequality in outcomes across socioeconomic spectrums. We investigated inequalities in low and high body mass index (BMI), anaemia, iron and folic acid supplementation, four or more antenatal care visits, institutional deliveries, and access to health services. Results Anaemia (−0.068 to −0.123), low BMI (−0.088 to −0.139), perceived distance to health services (−0.219 to −0.406), and needing permission to visit health facilities (−0.062 to −0.147) were concentrated among the less well-off, as shown by negative values. Iron and folic acid supplementation (0.043 to 0.230), antenatal care visits (0.260 to 0.495), and institutional deliveries (0.168 to 0.573) favored the better-off, as shown by positive values. Inequalities in urban vs. rural areas differed by indicator and country. Conclusions Nutritional status and health care inequalities among women followed patterns of socioeconomic disparities. Inequalities in nutritional status favored the better-off and educated women, and inequalities favoring the better-off were even greater for health care across countries.